Sistem Informasi Penjualan Berbasis Dekstop Pada Toko Baker Old - Alfian Amirullah; Nuraini Purwandari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Baker Old shop is one of the business locations for MSMEs engaged in the sale of a variety of breads that still uses traditional systems for processing sales data, stock data, and sales reports, making data processing time-consuming. The objective of this research is to develop a desktop-based sales information system that includes sales transactions, stock data input, and sales transaction reports. The employed method of system development is a prototype comprising system analysis using a cross-functional flowchart and a fishbone diagram, as well as system design using Unifed Modeling Language (UML) modeling. This research led to the development of a system that can be used to process sales transaction data, inventory data, and sales reports. The test results use black boxes in accordance with the Old Bakery's requirements.